Discourse Analysis toward News Texts on Fire Extinguishing Service of Kupang City in the Printed Mass Media of Timor Express - Ratna Katharina Lema (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2018)
This article examines news text on fire extinguishing of Kupang city in Timor Express to analyze its macro structure, super structure, micro structure and to describe the cognition and social context realized in it. I collected the data by taking the news texts of Timor Express purposively. Additionally I interviewed the editorial chief of the electronic mass media of the Timor Express to verify the data accuracy and to reach a deep understanding in enabling to provide details of the cognition and social contexts implicitly realised in the news text construction on fire extinguishing in the printed mass media of Timor Express. Results showed that the text structure of the Kupang City fire extinguishing service in Timor Express daily news consists of macro-structure, super-structure, and micro-structure. For the level of superstructure, in general Timor Express formulates headlines followed by leads consisting of script elements, which can be identified as: what, when, and who elements. Meanwhile, element why and how elements are in the news content (story). Macro structure is a thematic form of the Kupang city fire extinguishing service news text. The micro structure consists of semantics, syntactic, stylistic, rhetoric. In the microstructure of the news of the Kupang City fire service, the use of words that pointed to or reinforced news messages about the fire disaster that received fire services for the City of Kupang was found. In terms of social cognition, the aspect is realized in the form of journalists' mental awareness of a fire disaster that received services from the Kupang City fire service department. Timor Express journalists consider that fire is an unpredictable humanitarian disaster whose effects bring material losses in life. The social context relates to how a meaning is shared together. In accordance with the news text of the fire extinguishing service contains news of a fire accident and getting fire services from Kupang City.